2013
DOI: 10.1007/s10902-013-9477-0
|View full text |Cite
|
Sign up to set email alerts
|

What Would Your Parents Say? The Impact of Cohabitation Among Young People on Their Relationships with Their Parents

Abstract: Most European countries have seen a retreat from marriage, which is increasingly preceded or replaced by cohabitation. A question that arises in light of this trend is how the diffusion of non-marital cohabitation may affect the quality of family relations. This article investigates how cohabitation among young people affects their level of satisfaction with their relationship with their parents. We analyse data from the recently released Generation and Gender Survey for Poland, a country with a limited degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, previous research found lower levels of support-including financial and non-financial transfersbetween young cohabiting adults and their parents compared to singles or the married (Eggebeen 2005). Overall, support from parents may be more likely in contexts in which cohabitation is socially accepted and widespread (Baranowska-Rataj 2014;Schröder 2008).…”
Section: Cohabitation Wealth Premiummentioning
confidence: 83%
“…However, previous research found lower levels of support-including financial and non-financial transfersbetween young cohabiting adults and their parents compared to singles or the married (Eggebeen 2005). Overall, support from parents may be more likely in contexts in which cohabitation is socially accepted and widespread (Baranowska-Rataj 2014;Schröder 2008).…”
Section: Cohabitation Wealth Premiummentioning
confidence: 83%
“…However, our findings show that the small negative employment effects are present in the least developed subregions spread around the country, and have been accompanied by noticeable positive wage effects. Trade-offs between employment and wages have been reported by Baranowska-Rataj and Magda (2015) and Kamińska and Lewandowski (2015). However, those studies were based on annual labour market flows that were constructed using individual Polish labour force survey data.…”
Section: Introductionmentioning
confidence: 84%
“…In a collectivist country like India, where non-marital cohabitation is not popularly accepted, opting for a live-in relationship may lead to the disintegration of familial ties in a young person's family. According to Rataj (2014), this may lead to a decrease in life satisfaction and parent-child conflict may reduce the well-being of parents and adult children. In societies where marriage is recognized as the only moral way of family formation and livein relationships are considered as prohibited, the non-marital cohabiting couple is most probably to be despised for not following the traditional norms.…”
mentioning
confidence: 99%
“…However, the disparity between the social expectations of parents and the relationship choices of young adults do not automatically affect family attachment. In other words, the choice of being in a live-in relationship may not itself result in a decreased number of meetings or a lack of family support, even though it may yield some hesitation in relationships (Rataj, 2014). According to Rataj (2014), being in a non-marital cohabitation may adversely affect the amount of happiness and satisfaction which young couples derive from their relationship with their parents, and may harm their quality of life.…”
mentioning
confidence: 99%